ADMINISTRATIVE RESERVATION SYSTEM IN BEAUTIFUL TIARA WITH MICROSOFT VISUAL BASIC 6.0 - Andi Wibowo; Erik Orlando, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Problems faced by a company are many and complex, one of the administrativeproblems of booking. Administration booking is an activity data recording andstorage of transaction documents ordering the data which will later be processed insuch a way so as to produce the required information.To help overcome these problem author tries to make a reservation on AdministrativeSystems Beautiful Tiara Bags with Microsoft Visual Basic 6.0.Discussion on Administrative Systems Bags Order On Beautiful Tiara is divided intoseveral parts, namely making the proposed system (making the procedure proposedsystem, making the proposed system flowchart document, making the proposedsystem of data flow diagrams), creating entity relationship diagrams, normalizationmaking, making file specification , Making the menu structure, making the designinputs, design manufacturing output and manufacturing programs with Visual Basic6.0